Sea Level Variation Along the Western Coast of the Arabian Gulf - Sharaf el Din , S. H. (The International Hydrographic Review, 2015)
Observed hourly tidal heights from six stations during the period 1980-1987 were used in the analyses. Daily readings of the pressure at mean sea level from three meteorological stations were also used. The variations of the observed daily mean sea level were studied at the six stations, giving low values in the winter season, and high ones in summer and spring seasons. The monthly mean sea level showed higher values during July and August and lower ones in the winter season. As the Arabian Gulf is generally considered a shallow sea, the meteorological conditions are the main cause of the sea level variation. This was shown by the variation of the daily mean sea level residual at the six stations. From the analyses of the coherence of several parameters, the pressure difference over the Gulf area did not give a noticeable effect with either the daily observed sea level or the daily sea level residual. Generally speaking, the important factor affecting the sea level variation in the Arabian Gulf is the pressure system covering the area either during the summer or the winter seasons.